A CENTURY OF PUBLIC HEALTH POLICY IN IRAN: AN ANALYSIS OF INTELLECTUAL TRENDS IN IRAN'S DEVELOPMENT PLANS. (8th February 2017) - Doshmangir, Leila; Moshiri, Esmaeil
Abstract : Background and aims: Every individual is entitled to the right to health, and public health policies are the direct result of this principle. Both from a humanism perspective and due to the inherent requirements of a universal public health system, maintaining health has priority over treatment. Accordingly, any system aiming to promote public health must adjust its decisions, policies, and activities so as to continuously and progressively improve the quality of health services. The present research analyzes the role of Public health policies and intellectual trends in developing Iran's health system. The results can be used to outline the future of primary healthcare at different levels of health system. Methods: Data were gathered through a review of the literature as well as relevant documents and round table discussions. Data was analyzed using content analysis. Results: Clarification of health policies and distinguishing between key and ideal choices allows for more rigorous pursuit of the fundamental goals of the health system. Adherence to the guiding principles of a comprehensive health system, implementation of an all-inclusive network of health services, issues related to training human resources, the role of the government and the Ministry of Health in providing health services, and the basic needs of the health system are the most important factors that require more attention for further development of healthcare at different levels of Iran's health system. Conclusion: By analyzing the experiences of Iran's health system and by understanding the status quo, the strength and weakness of the system can be identified and a systematic approach can be taken to develop and implement new and better policies. Health issues are interrelated and are even affected by social conditions. Increasing the number of physicians, having extra funds, and building new hospitals with more beds are not as effective as promoting the concept of prevention in solving the problems that people faces today. The health system must be viewed as a whole made up of various intertwined parts. Its goals must be clarified, its requirements, resources, and limitations must be specified, and a systematic approach must be taken to solve the problems of the health system by taking into account all the contributing factors.